Effects of food type on the quality of spermatophores and subsequent cryopreservation and fertilization in banana shrimp - Memon, Abdul Jabbar (Terengganu: Universiti Malaysia Terengganu, 2014)
The goal of this study was to optimize spermatophores cryopreservation protocol of banana shrimp, Penaeus merguiensis. Spermatophores cryopreservation is a key topic in the development of reproductive technologies which provide the possibility to protect genetics of rare or beneficial species (gene banking), selective breeding, domestication, and conservation of stocks, and loss minimization during disease outbreaks.